Modelling of steering latencies and elasto-plastic deformation of the tires in vehicle trajectory prediction (2021)
In the recent years, the vehicle trajectory prediction had a great development as one of the main sources for pre-crash safety systems. This work explores the characteristics of the mechanical elements of the steering system and the elasto-plastic properties of the tires in the lateral response of a vehicle in a vehicleþs safety scenario. Thus, it was developed a model in MATLAB SIMULINK where different parameters and variables where analyzed in different times of the simulation.